Implementasi Bagi Hasil pada Usaha BUM Desa Perspektif Fatwa DSN NO. 115/DSN-MUI/IX/2017: Studi Kasus Di Desa Papaso Kecamatan Sosa Timur Kabupaten Padang Lawas - Suganti Hasibuan; Ardiansyah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the implementation of profit sharing in BUM Desa businesses from the perspective of DSN fatwa No.115/DSN-MUI/IX/2017 (case study in Papaso village, East Sosa sub-district, Padang Lawas Regency). The background is the form of cooperation carried out at BUM Desa Maju Mandiri in Papaso Village, where this cooperation involves more than two parties. BUM Desa in Papaso Village was established in 2022 with 3 (three) members. As for the implementation of BUM Desa activities in Papaso Village, there are problems in profit sharing or mudharabah between the capital provider and the manager, namely in this collaboration the capital provider should provide capital for the manager but the capital provider does not provide any capital at all. The capital provider is a third party from the community as an investor with an agreement at the beginning of profit sharing 50% for investors, 30% for managers and 20% for the village government. Based on the results of the study, the practice of profit sharing in Papaso Village, East Sosa District, Padang Lawas Regency is not in accordance with the DSN-MUI fatwa NO. 115/2017. 115/2017. To resolve this problem if you want to change the ratio by one of the parties, you must go through consensus deliberation to get an agreement. However, if one of the parties does not fulfill its obligations or there is a dispute between the parties, then the settlement is carried out through dispute resolution based on sharia with applicable laws and regulations after no agreement is reached through deliberation.